Lipid-Based Nanoparticle Formulation of Diallyl Trisulfide Chemosensitizes the Growth Inhibitory Activity of Doxorubicin in Colorectal Cancer Model: A Novel In Vitro, In Vivo and In Silico Analysis - Faris Alrumaihi; Masood Alam Khan; Ali Yousif Babiker; Mohammed Alsaweed; Faizul Azam; Khaled S. Allemailem; Ahmad A. Almatroudi; Syed Rizwan Ahamad; Mahdi H. Alsugoor; Khloud Nawaf Alharbi; Nahlah Makki Almansour; Arif Khan (Molecules, 2022)
Garlic’s main bioactive organosulfur component, diallyl trisulfide (DATS), has been widely investigated in cancer models. However, DATS is not suitable for clinical use due to its low solubility. The current study seeks to improve DATS bioavailability and assess its chemopreventive and chemosensitizing properties in an AOM-induced colorectal cancer model. The polyethylene glycol coated Distearoylphosphatidylcholine/Cholesterol (DSPC/Chol) comprising DATS-loaded DATSL and doxorubicin (DOXO)-encapsulated DOXL liposomes was prepared and characterized. The changes in the sensitivity of DATS and DOXO by DATSL and DOXL were evaluated in RKO and HT-29 colon cancer cells. The synergistic effect of DATSL and DOXL was studied by cell proliferation assay in the combinations of IC10, IC25, and IC35 of DATSL with the IC10 of DOXL. AOM, DATSL, and DOXL were administered to different groups of mice for a period of 21 weeks. The data exhibited ~93% and ~46% entrapment efficiency of DATSL and DOXL, respectively. The size of sham liposomes was 110.5 nm, whereas DATSL and DOXL were 135.5 nm and 169 nm, respectively. DATSL and DOXL exhibited significant sensitivity in the cell proliferation experiment, lowering their IC50 doses by more than 8- and 14-fold, respectively. However, the DATSL IC10, IC25, and IC35 showed escalating chemosensitivity, and treated the cells in combination with DOXL IC10. Analysis of histopathological, cancer marker enzymes, and antioxidant enzymes revealed that the high dose of DATSL pretreatment and DOXL chemotherapy is highly effective in inhibiting AOM-induced colon cancer promotion. The combination of DATSL and DOXL indicated promise as a colorectal cancer treatment in this study. Intermolecular interactions of DATS and DOXO against numerous cancer targets by molecular docking indicated MMP-9 as the most favourable target for DATS exhibiting binding energy of −4.6 kcal/mol. So far, this is the first research to demonstrate the chemopreventive as well as chemosensitizing potential of DATSL in an animal model of colorectal cancer.